2017
DOI: 10.2147/jpr.s153671
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and spinal TRPA1 channels contribute to formalin-induced long-lasting mechanical hypersensitivity

Abstract: BackgroundTransient receptor potential ankyrin 1 (TRPA1) is a non-selective cation channel expressed by a subset of nociceptive neurons that acts as a multimodal receptor. Its activity contributes to modulate nociceptive transmission in acute inflammatory pain. However, the role of this channel in chronic pain has been less studied. The purpose of this study was to investigate the local peripheral and spinal participation of TRPA1 channels in formalin-induced long-lasting hypersensitivity.Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
(71 reference statements)
2
9
1
Order By: Relevance
“…In line with our results, previous research described TRPA1-speci c neuronal responses after acute NTG 3 , and male rodents exposed to NTG were sensitive to TRPA1 antagonism 41 . Our ndings reveal an essential participation of TRPA1 for the development of chronic NTG hypersensitivity in male and female mice, in agreement with studies showing TRPA1 involvement in persistent pain sensitizations 8, [42][43][44] .…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, previous research described TRPA1-speci c neuronal responses after acute NTG 3 , and male rodents exposed to NTG were sensitive to TRPA1 antagonism 41 . Our ndings reveal an essential participation of TRPA1 for the development of chronic NTG hypersensitivity in male and female mice, in agreement with studies showing TRPA1 involvement in persistent pain sensitizations 8, [42][43][44] .…”
Section: Discussionsupporting
confidence: 91%
“…First, the neuronal expression of TRPA1 is highly sensitive to physiopathological conditions, especially inflammation. It was shown that a single subcutaneous injection of formalin or Complete Freund’s Adjuvant increased TRPA1 expression up to one-week post injection 19 , 20 . Moreover, ethanol, which we used as solvent for the retrotracer DiI, was shown to induce an inflammation associated with cyclooxygenase-2 upregulation in a model of gut inflammation 21 , 22 and therefore, could have affected TRPA1 expression in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…), and formalin injection increases the TRPA1 protein level in the DRG and spinal cord (Martinez‐Rojas et al . ). At the spinal cord level, exogenous stimulation of TRPA1 with allyl isothiocyanate or icilin substantially increases glutamate release to lamina II neurons (Kosugi et al .…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown recently that peripheral and intrathecal injection of A‐967079, a specific TRPA1 antagonist, can reverse pain hypersensitivity caused by formalin injection (Martinez‐Rojas et al . ). These findings indicate that in addition to functioning as a transducer for tissue inflammation, TRPA1 at the spinal cord level is endogenously activated to maintain nociceptive drive to lamina I neurons in chronic inflammatory pain.…”
Section: Discussionmentioning
confidence: 97%